Climate change scenario in Indian hot arid region - Singh, D. V.; Meena, H. M.; Kumar, Mahesh (Indian Farming, 2018)
Emission of greenhouse gases is increasing since the beginning of Industrial Revolution, and their increasing concentrations in the atmosphere are altering the radiative forcing of the earth. The climate change due to earths’ altered energy balance resulted in increasing temperatures and changes in precipitation amounts, frequency of extreme weather events, rise in sea levels, etc. globally. Increase in day and night temperatures was observed in hot arid zone, particularly after 1970s. Consequently, number of hot days in a year is increasing, whereas the number of cool nights is declining. Annual rainfall showed clear increasing trend (9.4 mm yr-1) in Saurashtra and Kutch regions during 1981-2010 and maximum increase was observed in July rainfall (3.2 mm yr-1). Climate models showed that warming would continue in these regions in near future also, but the magnitude may vary depending upon future emission scenario. The impact of climate change on precipitation in arid regions of India, however, is not so clear though there are indications of slight increase.